Managing substance abuse on psychiatric units: a scoping review - Hudon, Alexandre; Cloutier-Tanguay, Jean-Philippe; Levy, Joshua; Dastous-Stampe, William; Daigneault, Marie-Louise; Lacombe, Cédric; Noël, François; Borduas Pagé, Stéphanie (Frontiers in Psychiatry, 2025)
ObjectiveSubstance use during psychiatric hospitalization compromises safety, treatment engagement, and post-discharge outcomes, but practical guidance for ward staff remains limited. This scoping review mapped the peer-reviewed literature on how psychiatric inpatient units detect, manage, and respond to alcohol or drug use that occurs on the ward itself, and summarized the effectiveness and breadth of reported strategies.MethodsThe review followed the PRISMA-ScR framework. PubMed, Embase, PsycINFO, and Google Scholar were searched from inception to April 2025 using controlled vocabulary and free-text terms for substance use, psychiatric inpatients, and management strategies. English- and French-language empirical studies, quality-improvement reports, policy evaluations, and scoping reviews were eligible if they described an intervention or protocol applied in an inpatient psychiatric setting. Reviewers independently screened titles/abstracts and full texts extracted data with a standardized spreadsheet, and applied Joanna Briggs Institute critical-appraisal tools.ResultsFrom the identified studies, 18 studies met inclusion criteria: 1 randomized trial, 3 quasi-experimental reports, 8 descriptive prevalence/cross-sectional studies, 2 policy case studies, 3 reviews/chapters, and 1 commentary. Seven recurring intervention domains were identified: systematic screening (n = 9 studies), brief motivational interventions, policy / protocol development, environmental or security measures, harm reduction strategies, staff training and culture change, and discharge planning. Structured screening improved detection rates up to two-fold; brief interventions such as SBIRT and BIMI increased post-discharge treatment engagement and reduced 30-day readmissions by up to 18%. Zero-tolerance security measures showed inconsistent effects on contraband entry or aggression. Overall methodological quality was moderate, with most evidence derived from single-site implementations.ConclusionsExisting evidence suggests that standardized screening, ward-adapted brief interventions, clear patient-centered policies, and targeted harm-reduction measures can feasibly improve management of inpatient substance use, while purely punitive security tactics are insufficient. Research gaps include rigorous multi-site evaluations, adolescent and forensic settings, and integrated harm-reduction protocols for substances other than nicotine.